ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN PADA BANK UMUM GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2015-2017 - Lika Handayani; Ronny Malavia Mardani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTBanks are financial institutions whose business activities are to raise funds from the publicand redistribute the funds to the community and provide other bank services. Profitability as one of the references in measuring the amount of profit becomes so important to know whether the company has run its business efficiently. The purpose of this study is to find out the factors that affect the profitability of banks at commercial banks going public. The population in this study were 43 banks listed on the Stock Exchange. The sample in this study were 31 banks. The data analysis used in this study is multiple linear regression analysis. The results of multiple linear regression analysis are NIM and BOPO have a positive and significant effect on ROA, LDR and CAR has a not significant positive effect on ROA, NPL has a significant negative effect on ROA.keywords: ROA, NIM, BOPO, CAR, LDR, dan NPL.